Penggunaan Multimedia Interaktif Berbasis Android sebagai Media Pembelajaran Tari Tanggai di SMA - Angelysca, Rachel (CV. ITTC INDONESIA, 2026)
This study aims to analyze in depth the effect of the implementation of the use of Android-based interactive multimedia as a learning medium for Tanggai Dance on the learning outcomes and learning motivation of students at SMA Negeri 1 Kikim Selatan. The study used a quantitative approach with a quasi-experimental method and a pretest–posttest control group design. The research sample consisted of two classes, namely the experimental class (n = 30) and the control class (n = 30). The results of the analysis showed that the average pretest score of the experimental class was 65.20 and increased to 82.40 in the posttest, an increase of 26.38%. Meanwhile, the average score of the control class increased from 64.80 to 71.10 or 9.72%. The t-test results showed that the t-value = 4.87 was greater than the t-table = 2.00 at a significance level of 0.05, so there was a significant difference between student learning outcomes in the experimental class and the control class. In addition, the questionnaire results showed that 86.7% of students were in the high learning motivation category. These findings demonstrate that Android-based interactive multimedia has a significant and effective impact on enhancing Tanggai Dance learning in secondary schools.